2016
DOI: 10.5603/kp.a2015.0212
|View full text |Cite
|
Sign up to set email alerts
|

Gender and quality of life and coping over one year after myocardial infarction: do men really have the upper hand?

Abstract: A b s t r a c tBackground: Multiple reports have confirmed that quality of life (QoL) in women after myocardial infarction (MI) is worse compared to men of the same age but some variation depending on QoL dimension was also reported. A less studied issue is coping after MI. Aim:The present study examined whether gender affected the level and dynamics of QoL and coping over 1 year after MI. Methods:This questionnaire-based study included 3 stages, at the beginning and the end of a rehabilitation programme (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
8
1
1
Order By: Relevance
“…Unfortunately, the delayed positive effect of problem solving is counterbalanced by a negative effect of resignation at T3. We also observed that substance use at T2 was a delayed positive predictor of T3 discomfort in women; there were no gender or time differences in use of this strategy [28]. In women substance use at T2 was negatively related to T2 symptoms, after controlling for variance in symptoms at T1.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Unfortunately, the delayed positive effect of problem solving is counterbalanced by a negative effect of resignation at T3. We also observed that substance use at T2 was a delayed positive predictor of T3 discomfort in women; there were no gender or time differences in use of this strategy [28]. In women substance use at T2 was negatively related to T2 symptoms, after controlling for variance in symptoms at T1.…”
Section: Discussionmentioning
confidence: 47%
“…We observed that resignation predicted HRQoL at T1 and T2 in women and at T3 in men. However, in our sample there was no gender difference in the dynamics of use of this strategy, although women made more use of resignation than men at T2 [28]. This shows that even when there is no gender difference in use of a coping strategy, there may be a gender difference in how it is related to HRQoL.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The Polish adaptation of the Life Orientation Test-Revised (LOT-R) was used to measure optimism [26,27]. It consists of 10 items describing beliefs about the future.…”
Section: Procedures and Research Toolsmentioning
confidence: 99%
“…Coping strategies were measured using a modi ed version of the COPE questionnaire [27,28] consisting of 46 statements organised into seven subscales. Answers were given on a scale ranging from 1; 'I don't usually do this at all' to 4; 'I usually do this a lot'.…”
Section: Procedures and Research Toolsmentioning
confidence: 99%